Representações sociais do vitiligo: dimensões simbólicas da marca branca - Bú, Emerson Araújo Do (2018)
Vitiligo is a disease with a complex and non-consensual etiology, affecting up to 2% of the world population, characterized by the formation of white spots, through the skin depigmentation. Consensually, it is understood that it presents asymptomatically in the physical-organic dimension of the one who has it. Nonetheless, the whitish macules provoke estrangement subjective and intersubjective experiences, caused, most of all, by their exposure in the social context. Thus, it can be said that Vitiligo is not just another skin disorder, but it is, above all, a social object that generates Social Representations (SR), which serve as guides for behavior towards it. In this context, considering that most studies developed on the subject focus on biological aspects of the skin illness process and, consecutively, demonstrating the literature incipience that apprehend the condition in an holistic way, this dissertation aimed to broaden the Vitiligo understanding from the point of view of who owns it, considering their values, perceptions, opinions and ideas. To do so, two empirical studies were carried out. The first one aimed at apprehending the SR of Vitiligo elaborated by people who have such infirmity. In this, 196 Brazilians with Vitiligo participated, from all country regions, with ages ranging from 18 to 70 years (M=38.85, SD=12.53), predominantly female (70.02%), through the online response of a sociodemographic questionnaire and the question: "For you, what is Vitiligo?". The Descending Hierarchical Classification and Similitude Analysis of the collected material allowed identifying multifaceted approaches to the disease understanding, in which the content emerged through the speech of social actors anchors the disease comprehension sometimes to the dermatological/biomedical knowledge, or the psychodermatological knowledge. The second study aimed to identify the core nucleus and peripheral elements of the Vitiligo's SR, as well as the self-image that people with the disease have. It was attended by 370 participants from all Brazil regions, aged 18-67 years (M=35.71; SD=12.11), predominantly female (80.7%), through the online resolution of a sociodemographic questionnaire and the Free Word Association Technique (FWAT). It is noteworthy that in the FWAT the participants' responses were given from the inductors "Vitiligo" and "myself", the latter being related to the perception that the person with the disease has about him/herself. The results indicated, through the prominence of psychosocial evocations, that Vitiligo's marks are not restricted to the skin, but overlap it, since having them, in the stigmatizing and prejudiced social dynamics, negatively affects social experiences, the self-image and the self-esteem of the people with the illness, causing self-deprecating feelings characteristic in the self-stigmatization. In general terms, the two empirical studies results have shown that the Vitiligo understanding is permeated by biopsychosocial dimensions. These are significant and innovative contributions to the disease understanding, approaching the Social Psychology to the Health Psychology, insofar as it is connected to the dermatology knowledge.